2013
DOI: 10.1007/s11102-013-0519-8
|View full text |Cite
|
Sign up to set email alerts
|

Patient-focussed outcomes in acromegaly

Abstract: BackgroundHealth-related quality of life (QoL) is severely impaired in acromegaly due to the physical and psychological consequences of the disease. Pharmacological and surgical treatments, when available, can improve QoL and life expectancy.Case descriptionA 34-year-old male with uncontrolled acromegaly due to a large and invasive macroadenoma, which could not be resected by transsphenoidal surgery. Over 9 years, he had limited access to pharmacological interventions and persisted with clinically and biochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…(14,15) Additionally, from the patient's perspective, symptoms and QoL are critical parameters of disease control (6, 12), therefore they should be assessed in clinical practice for an adequate long-term management of acromegaly. (13) Discrepancy between patient's and physician's ratings of general health status has been previously demonstrated. (6,16,17) The consequence of such a discordant viewpoint regarding disease activity is that decisions are often prone to not being shared between patients and physicians (16).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…(14,15) Additionally, from the patient's perspective, symptoms and QoL are critical parameters of disease control (6, 12), therefore they should be assessed in clinical practice for an adequate long-term management of acromegaly. (13) Discrepancy between patient's and physician's ratings of general health status has been previously demonstrated. (6,16,17) The consequence of such a discordant viewpoint regarding disease activity is that decisions are often prone to not being shared between patients and physicians (16).…”
Section: Introductionmentioning
confidence: 95%
“…Even when biochemical control is achieved, many patients still suffer from physical and psychological residual morbidity that can lead to persistently impaired QoL. (6, [12][13][14] In fact, the correlation between "biochemical" severity (measured by IGF-1 levels) and impact of disease on patient's lives is weak. (14,15) Additionally, from the patient's perspective, symptoms and QoL are critical parameters of disease control (6, 12), therefore they should be assessed in clinical practice for an adequate long-term management of acromegaly.…”
Section: Introductionmentioning
confidence: 99%
“…In these individuals, factors such as being female, duration of the disease [ 3 ], age, and radiotherapy [ 4 ] have been negatively associated with QoL. Although improvement in QoL may be achieved with drug therapy or surgery [ 5 , 6 ], physical and psychological morbidities may impair QoL, even in acromegalic patients in long-term biochemical remission (i.e., patients with controlled disease) [ 7 , 8 ]. Therefore, the data on the correlation between disease control and QoL in acromegaly are controversial [ 9 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Few studies indexed in MEDLINE were found on this subject in Latin America. We found a single case report from Argentina [ 5 ] and one study with 50 patients from Mexico [ 8 ]. In this study, we aimed to identify the factors associated with quality of life in patients with acromegaly with follow-up at the referral service in neuroendocrinology of the state of Maranhão, northeast of Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…These skin changes are well known to impair the quality of life in patients with acromegaly. 8,13 Therefore, we want to investigate whether transsphenoidal surgery of GH-producing adenoma leads to a decrease in CVG in patients suffering from acromegaly related to the levels of IGF-1.…”
Section: Introductionmentioning
confidence: 99%